<h3><em><u>Simplify -3y+2x-5y-7x is:</u></em></h3><h3>-8y - 5x</h3>
<em><u>Solution:</u></em>
<em><u>Given that, we have to simplify</u></em>
![-3y + 2x-5y-7x](https://tex.z-dn.net/?f=-3y%20%2B%202x-5y-7x)
We can simplify the above expression by combining the like terms
Like terms are terms that has same variable ( with same exponent) with same or different coefficient
From given,
![-3y + 2x-5y-7x](https://tex.z-dn.net/?f=-3y%20%2B%202x-5y-7x)
Here, like terms are -3y and -5y
And 2x and -7x
Group the like terms
![-3y-5y+2x-7x](https://tex.z-dn.net/?f=-3y-5y%2B2x-7x)
Combine the like terms
![-8y -5x](https://tex.z-dn.net/?f=-8y%20-5x)
Thus the given expression is simplified
Answer:
The initial height of an object above ground before being launched straight up in the air
Step-by-step explanation:
we have
![h(t)=-16t^{2}+110t+72](https://tex.z-dn.net/?f=h%28t%29%3D-16t%5E%7B2%7D%2B110t%2B72)
we know that
The number 72 represent the y-intercept of the function
The y-intercept is the value of y when the value of x is equal to zero
In this problem
The value of h when the value of t is zero
Therefore
The initial height of an object above ground before being launched straight up in the air
3/4= j-1/2
first to add 1/2 to both sides to solve for j
3/4 + 1/2= j
second you find a common denominator in order to add 3/4 and 1/2, the common denominator would be 4, you would have to change 3/4 at all because the denominator is already 4 but in order to make the denominator of 1/2, 4 you would have to multiply both the denominator and numerator by 2 so
3/4 + 2/4 = 5/4
so 5/4 =j
to check your answer you plug 5/4 in for j
3/4 = 5/4 -1/2
again you need to find a common denominator between 5/4 and 1/2 which again would be 4, and again you wouldn't change 5/4 but you would multiply both the numerator and the denominator of 1/2 so
3/4= 5/4-2/4
5-2= 3 and you would keep the 4 so
5/4 - 2/4 = 3/4
so j = 5/4
Beachside it is supposed to be 619 into that form
Hello!
First you find the common difference in the sequence
6 - 12 = -6
0 - 6 = -6
The common difference is -6
We can now make the equation
-6(n - 1) + 12
we got the 12 because it is the first number in the sequence
Simplify
-6n + 6 + 12
Simplify
18 - 6n
The answer is B) an = 18 - 6n
Hope this helps!